I Am There … but Not Quite: An Unfaithful Mirror That Reduces Feelings of Ownership and Agency. (February 2018) - O'Sullivan, Noreen; de Bezenac, Christophe; Piovesan, Andrea; Cutler, Hannah; Corcoran, Rhiannon; Fenyvesi, David; Bertamini, Marco
The experience of seeing one's own face in a mirror is a common experience in daily life. Visual feedback from a mirror is linked to a sense of identity. We developed a procedure that allowed individuals to watch their own face, as in a normal mirror, or with specific distortions (lag) for active movement or passive touch. By distorting visual feedback while the face is being observed on a screen, we document an illusion of reduced embodiment. Participants made mouth movements, while their forehead was touched with a pen. Visual feedback was either synchronous (simultaneous) with reality, as in a mirror, or asynchronous (delayed). Asynchronous feedback was exclusive to touch or movement in different conditions and incorporated both in a third condition. Following stimulation, participants rated their perception of the face in the mirror, and perception of their own face, on questions that tapped into agency and ownership. Results showed that perceptions of both agency and ownership were affected by asynchrony. Effects related to agency, in particular, were moderated by individual differences in depersonalisation and auditory hallucination-proneness, variables with theoretical links to embodiment. The illusion presents a new way of investigating the extent to which body representations are malleable.